Transfusion transmitted malaria in a thalassaemia major patient - Anuar, Nur Aliaa; Nik Mustapha, Nik Hafidzah; Seman, Zainina (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Blood safety is a major global issue. Transfusion transmitted parasitic infections (TTPI) like malaria are rare and possibly under-reported, a situation which could be attributed to lack of awareness of the mosquito-borne transmission of infection. Such infections are still considered potential health hazards, as they can pose a significant threat especially in immunocompromised patients, where they have proven to be fatal. Prevention of the transmission depends solely on the donor’s questionnaire which addresses previous or current infection with aetiologic agents. Donor deferral is effective however clear guidelines are needed. This case report features the transfusion-transmitted of Plasmodium Falciparum in a 15-year-old splenectomised patient with underlying beta thalassaemia major.